Enhanced CO oxidation reaction over Pt nanoparticles covered with ultrathin graphitic layers. (May 2016) - Gao, Lijun; Fu, Qiang; Li, Jiamin; Qu, Zhenping; Bao, Xinhe
Abstract: It has been empirically established that graphitic carbon deposits often result in deactivation of metal catalysts due to the physical blockage of surface active sites. Our recent surface science works however demonstrate that molecules such as CO can adsorb on Pt(111) surface covered by graphene overlayers via an intercalation process, and surface reactions e.g. CO oxidation have been enhanced by the graphene covers. In this work, supported Pt nanocatalysts were coated by ultrathin graphitic carbon layers through chemical vapor deposition process forming Pt@C core–shell nanostructures, which were confirmed by characterizations of Raman spectroscopy, temperature-programmed oxidation and transmission electron microscopy. CO oxidation over the Pt@C catalysts shows a lower apparent activation energy compared with the pure Pt catalysts, and in-situ infrared studies indicate that the reactions occur under the graphitic shells. The present results suggest that coating metal nanocatalysts with ultrathin graphitic overlayers may be used to promote metal catalyzed reactions.